Burnout and sleep quality among community health workers during the pandemic in selected city of Andhra Pradesh - Tanuja Yella; Mackwin K. Dmello (Elsevier, 2022)
Background: This pandemic has resulted in physical and emotional exhaustion among everyone, especially among community healthcare workers (CHWs), resulting in increased burnout and poor sleep quality. This pandemic has increased responsibilities for Accredited Social Health Activist (ASHA) workers and Auxiliary Nurse Midwife (ANM) at the grassroots. Previous studies have shown that infectious diseases like SARS and MERS directly affect sleep. With the COVID-19 pandemic, burnout and poor sleep among healthcare workers are expected to increase. Aim: To determine the prevalence of burnout and sleep quality among community health workers Settings: and Design: This Cross-sectional study was conducted from February to April 2020 in Urban Primary Health care centres of Guntur city, Andhra Pradesh. Methods and material: Copenhagen Burnout Inventory scale (CBI) with a 5-point Likert scale and Pittsburgh Sleep Quality Index (PSQI) Questionnaire were used among four hundred and ten study participants. Descriptive statistics and the Chi-square test were used; a p-value of ≤0.05 is considered significant. Results: The prevalence of personal burnout was 16.8%, while work-related and pandemic-related burnouts were 10.5% and 25.4%, respectively. The prevalence of poor sleep quality was 35.09%. Fear of contracting the virus was present among 38.3%. Fear of infecting the family members because of their exposure was reported by 36.6% of the respondents; 71.7% and 79.3% reported receiving support from the organisation and colleagues, respectively. Conclusions: The provision of necessary equipment, regular check-ups and timely interventions will minimise the risk of stress and burnout.